KAITAN HUKUM ISLAM DENGAN PERKEMBANGAN ILMU PENGETAHUAN DAN TEKNOLOGI - M. Sabir U. (State Institute of Islamic Studies (IAIN) Palu, 2007)
During the prophet’s life, all legal problems would be returned to him. Then, he would make a decision on those problems. It is different from our contemporary era since the prophet has passed away while there are some problems brought about by the development of science and of technology. For example, transplantation and insemination, both of which should be discussed by Muslim scholars to determine whether or not both are permitted by Islam. If both are banned or are permitted, then what are the conditions for banning or permitting them. Within this context, this article elaborates the relationship between Islamic law and the development of science and of technology.Kata Kunci : hukum Islam, ilmu pengetahuan, teknologi